Evaluation of Barriers to Entrepreneurship Development: A Comparative Student Survey - Walczyna, Anna; Arent, Anna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: The research aimed to answer questions on how students evaluate the external conditions for starting a business in Poland, what variables differentiate their perceptions and whether these evaluations change over time. Research Design & Methods: The surveys were conducted in the years 2016–2017 (517 people) and 2022–2023 (382 people) on a sample of students at the Lublin University of Technology using the same survey questionnaire. The following statistical methods were used to develop the results: descriptive statistics, factor analysis and the Mann-Whitney U test. Findings: The research revealed the existence of four barriers to entrepreneurial development: legal, labour market, financial, and market. The barriers identified were rated higher in study one. Additionally, a pandemic barrier was diagnosed in group two. In the first study, work experience proved to be the variable that most differentiated the assessment of the barrier. The second is the area and level of study and entrepreneurial tradition. Implications / Recommendations: The research shows that both studies identified analogous categories of barriers but with a slightly different structure. The assessments of the perception of business conditions made by the surveyed student-potential entrepreneurs are complemented by the opinions of already operating entrepreneurs on the impact of the external environment on entrepreneurship development. Knowledge acquired through education and professional work proved to be an important feature influencing the way barriers were assessed. These results can be helpful when making changes to educational programmes concerning business knowledge, internships and work placements. Contribution: Expanding and completing the knowledge of the perception of the impact of external conditions on entrepreneurship development.